-5(-3x-3)+5x+4=-1

Simple and best practice solution for -5(-3x-3)+5x+4=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(-3x-3)+5x+4=-1 equation:



-5(-3x-3)+5x+4=-1
We move all terms to the left:
-5(-3x-3)+5x+4-(-1)=0
We add all the numbers together, and all the variables
5x-5(-3x-3)+5=0
We multiply parentheses
5x+15x+15+5=0
We add all the numbers together, and all the variables
20x+20=0
We move all terms containing x to the left, all other terms to the right
20x=-20
x=-20/20
x=-1

See similar equations:

| 7+9d=70+3 | | -15=6y-15 | | Y=314/2,07x | | 6a=6a-21 | | 5x+10=300 | | 6+y/5=-24 | | 2x+4)=14 | | 90=4x+3x+12 | | -4x(-2x+5)-5x+5=-24 | | x={8,-7} | | 9q+8=q+72 | | 2x+9=3× | | -2(x+3)+4x-4=-14 | | 8(x+30)=8 | | 4(y+1=y+13 | | 9=3/3y | | -4(x+5)+3x-1=−13 | | -27=-7w+3(w-5) | | 9+11x=152 | | -3x-397+6x)=7(1-4x) | | (k+5)-k/4=54 | | −4(2x−4)−2x−2=−36 | | 3x-4=6x-28 | | 7x-42=2x-2 | | -4=7(x+4)-3x | | 2x^2-12=64 | | 2x+x=927 | | ((x+4)/5)+((x+1)/7)=1 | | 2x+5=0.5(4x+10) | | x+(x-11)=43 | | 39-v=56 | | 3x-4x+8=-5x+4x-9 |

Equations solver categories